STRUKTUR IKLAN PARFUM ECLAT FOR MEN PADA KATALOG ORIFLAME - Dewa Ayu Kadek Claria; I Gusti Ngurah Adi Rajistha (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2019)
ABSTRACT The purpose of this research is to identify “The structure of Eclat for Men’s Perfume in Oriflame Catalogue” because the structure is an interesting topic to discuss. The problem analyzed in this research is what kinds of structure found in Eclat for Men’s Perfume found in Oriflame Catalogue. The theory used in this research is theory by Leech about structure of advertisement which consists of headline, body copy, signature line dan standing details. This research is also limited on commercial advertisement on men’s perfume entitled Eclat for Men’s which is obtained from the Oriflame Catalogue. The result shows that Eclat for Men’s Perfume has a complete structure. They are headline, illustration, body copy, signature line dan standing details. For the next research commercial advertisement on electronic media should be reviewed in the terms of semiotic. Keywords: Text, Systemic Functional Linguistics, Commercial Advertisement